PENGARUH KULIT BUAH NAGA (Hylocereus polyhizus) DALAM PAKAN TERHADAP KINERJA PRODUKSI IKAN KOI (Cyprinus carpio) - Teuku Reza Efianda; Yusnita Yusnita; Nurul Najmi; Kiki Rishki Ananda; Fazril Saputra (Universitas Teuku Umar, 2020)
This study aims to determine the rate of growth, survival, and feed conversion ratio in feed of Cyprinus carpio with Hylocereus polyhizus. This study used a Completely Randomized Design (CRD) consisting of 4 treatments and 4 replications. The treatments in this study include 0% (P0), 5% (P1), 10% (P2), and 15% (P3). The method of feeding uses 5% feeding rate with a frequency of three times a day (morning, afternoon, evening). The research parameters observed included survival, specific growth rate, feed conversion ratio and water quality. Quantitative research results showed the best survival at P3 of 92.5%, the best specific growth rate at P3 treatment was 0.04 g / day, the best feed conversion ratio at P3 was 1.06, while the results of qualitative research on water quality showed temperature, pH, Dissolved Oxygen is in optimal condition according to the water quality of koi fish. The conclusion of the 15% treatment study (P3) is the best dose of Hylocereus polyhizus substitution of Cyprinus carpio with increased survival and specific growth rate, and decreases the rate of feed conversion ratio. Keywords: Cyprinus carpio, Growth, Hylocereus polyhizus, Production, Survival Rate.